Robotic complete mesocolic excision using indocyanine fluorescence imaging in colorectal cancer: A case study and technical approach. (2020) - Young, R.; Rajkomar, A.K.S.; Smart, P.; Warrier, S.K.
Highlights: Complete mesocolic excision confers a possible survival advantage in right sided colorectal cancer. Indocynanine Green (ICG) Fluorescence Imaging may allow for more targeted lymph node clearances. Robotic surgery allows for these nodes to be removed with an MIS approach. Abstract: Introduction: Colorectal cancer is the second most common malignancy in developed countries and accurate staging is vital for determining the most appropriate management plan, in particular, whether adjuvant chemotherapy is recommended in addition to surgical resection. There is currently no consensus regarding standard practice for lymph node resection in colorectal cancer although there is increasing evidence to support the use of sentinel lymph node mapping to target lymph node sampling and facilitate ultra-staging of nodes. Presentation of case: We present the case of a 49 year old female who underwent a robotic right hemicolectomy and complete mesocolic excision for caecal adenocarcinoma using indocyanine fluorescence imaging (ICG FI) to guide nodal dissection. Discussion: ICG FI may be useful for sentinel lymph node mapping in colorectal cancer. This technique can assist to identify the first draining lymph nodes and permit ultra-staging of lymph nodes. Conclusion: While there is still limited evidence to support ICG FI, the current body of literature suggests that it is likely to be a feasible and sensitive technique for guiding sentinel lymph node sampling in colorectal cancer.